CHALLENGES OF ECONOMIC DIPLOMACY AT THE BEGINNING OF THE XXI CENTURY: CONCEPT, DIVISION AND SIGNIFICANCE: - - Maksimović, Marijana (Political Review, 2023)
At the beginning of the XXI century, we are witnessing great changes, caused by crises, conflicts in the world, and epidemics that change our way of life and work. In recent years, digitalization has progressed so much that it has affected the organization of work and contributed to the way many companies operate differently. Rightfully so, people begin to wonder if they can continue to manage their lives or if they will be forced to surrender to the waves of circumstances created "outside". In this context, there was a change in economic diplomacy, which also faced challenges that affected it so its role and its importance increased. As geoeconomics separated from geostrategy, economic diplomacy gained more importance. Today, international economic policy and economic diplomacy have become as important as the classical issues of peace, security, and general prosperity. Economic diplomacy takes place at all levels, at which classical diplomacy also takes place, but it deals exclusively with economic topics, related to competitiveness, profitability, supply of raw materials, and energy. The author starts from the assumption that there have been major changes in international economic relations in the last decade and that they have significantly influenced the importance and improvement of economic diplomacy. The method of description and analysis was used in the work, and the scientific contribution is reflected in the area of strengthening the economic national identity of a country in international economic relations. Furthermore, the obtained conclusions can serve Serbia for better positioning in terms of international concreteness, but also for the advancement of national economic interests. The aim of this paper is to highlight the emerging challenges in economic diplomacy during the last thirty years. Economic diplomacy became an important tool in international business relations, promoting national companies, products, and services, but also many other forms of economic cooperation in the XXI century.